Genesis [compact disc, unabridged] - Cook, Robin, 1940- (Penguin Audio, an imprint of the Penguin Random House Audio Publishing Group, 2019)
When the body of twenty-nine-year-old social worker Gloria Montoya, seven weeks pregnant with her first child, shows up on Chief New York City Medical Examiner Laurie Montgomery's autopsy table, she's baffled to find no apparent causes of death. With no clues to go on, Laurie enlists the help of Dr. Tricia Albanese, a forensic pathology resident with a background in genetic science, to help her trace the identity of the unborn baby's father using DNA from the mother and child. But when Tricia is found dead in her apartment in a manner strikingly similar to Gloria's death, Laurie realizes she might have two linked homicides on her hands.